PENINGKATAN PENGETAHUAN TENTANG BAHAYA PENGGUNAAN BAHAN TAMBAHAN PANGAN YANG DILARANG TERHADAP KESEHATAN PADA SISWA SMA N 1 GUBUG - Triminarsih Tri (Jurnal Pengabdian IKIFA, 2024)
Many snacks sold around schools are generally unsafe. Colorings, sweeteners and preservatives are types of food additives. These additional ingredients are often found in every snack food sold around the campus or around the school environment. Based on a survey conducted by the team before the service event was held, in SMA N 1 Gubug there were still many foods and drinks being sold that were suspected to contain dangerous BTP. This is what prompted the service to carry out an outreach event related to the dangers of prohibited food additives for the health of SMA N 1 Gubug students. The outreach event was attended by 34 students, 19 women and 34 men. The results of the service event showed an increase in pretest and posttest service points by 40 points. It is hoped that students will gain additional knowledge about the dangers of BTP for health and improve their snack patterns in the future.